The effects of chromolaena odorata chloroform extract on pseudomonas aeruginosa biofilm / Mohamad Shamil Anwar Ibrahim - Ibrahim, Mohamad Shamil Anwar (2016)
Pseudomomas aeruginosa infection is especially prevalent among patients with burn wound, cystic fibrosis, acute leukemia, organ transplants and intravenous-drug addiction. The most serious infections include malignant external otitis, endhophthalmitis and more. At the same time, there are several reports on antibacterial properties of Chromolaena odorata plant extract. However, it remains uncertain whether C. odorata could control P. aeruginosa infections especially the biofilm growth. It is still unknown how the C. odorata plant extract potentially modulate the proteome level in P. aeruginosa biofilm. This study was carried out to determine the antibiofilm activity of C.odorata chloroform extracts (COCE) against P.seudomonas aeruginosa under aerobic and anaerobic conditions. There are several reports on antibacterial properties of COCE. Phytochemical screening using gas chromatography mass spectrometry (GCMS) revealed one of the major compound in COCE was Germacrene D. Based on micro broth dilution assay performed, oxygen level did not show any effect towards the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of COCE against P. aeruginosa. However, antibacterial susceptibility test showed that the antibacterial activity of COCE against P. aeruginosa under anaerobic condition higher than aerobic conditions. Colony forming unit (CFU) counting of biofilm cells demonstrated that COCE had greater antibiofilm activity against P. aeruginosa under aerobic condition. Subsequent, treatment C. odorata chloroform extract resulted in changes in the biochemical composition of P. aeruginosa biofilm fraction under both experimental conditions, as indicated by variation in infrared (IR) spectra in the region between 1700 cm-1 and 900 cm-1. The cytoplasmic proteins expressed by P. aeruginosa biofilm upon treatment with COCE extract were profiled. The treatment of COCE resulted in changes in the profile of cytoplasmic proteins of P. aeruginosa biofilm under aerobic and anaerobic condition. The treatment of COCE resulted in changes in the profile of cytoplasmic proteins of P. aeruginosa biofilm under aerobic and anaerobic condition. By using MALDI-TOFTOF for protein profiling, about 24 proteins was identified. For example phosphogluconate, fumarate hydratase class II 1, elongation factor Tu 1 and more.